Diagnostic Value of Narrow Band Imaging in Visualization of Pathological Lesions in Larynx and Hypopharynx - Jana Šatanková; Lucia Staníková; Anna Švejdová; Michal Černý; Jan Laco; Viktor Chrobok (Acta Medica, 2021)
Introduction: Narrow Band Imaging (NBI) is an endoscopic optical imaging enhancement technology that improves the contrast of mucosal surface texture and enhances visualization of mucosal and submucosal vasculature. Due to its properties, it can visualize suspected malignant or precancerous lesions earlier than conventional white light endoscopy. The aim of this study was to analyze the benefit of NBI in visualization of precancerous and malignant lesions in preoperative and intraoperative diagnostics and correlation with histopathologic results. Methods: A total of 589 patients with suspicious laryngeal or hypopharyngeal lesion were investigated using conventional white light endoscopy (WLE) and NBI endoscopy with high-definition TV (HDTV NBI) from 10/2013 to 12/2019. Patients were divided into two groups based on pre-operative NBI examination (group A, 345 patients) and intraoperative NBI examination (group B, 244 patients). All suspicious lesions were graded to 5 types of Ni classification and correlated with histopathologic results. The SPSS version 8.0.4 statistical software package was used for statistical analysis. In diagnosing premalignant and malignant lesions sensitivity, specificity, positive predictive value, and negative predictive value were calculated. Results: The agreement between NBI endoscopy and histopathological analysis in group A was statistically significant (Қ = 0.76, p < 0.001), with a sensitivity of 86.2% (95% IS: 65.4–95.2) and specificity of 90.9% (95% IS: 70.6–94.1). Moreover, in group B was proven almost perfect agreement between NBI and histopathological analysis (Қ = 0.8461, p < 0.001), with a sensitivity of 84.0% (95% IS: 60.2–92.4) and specificity of 96.0% (95% IS: 87.0–99.2). Conclusions: Based on our results, NBI using the Ni classification has great potential in improving diagnosis of precancerous and malignant lesions and correlates strongly with histopathologic results. It serves as a useful adjunct to white light endoscopy in the diagnosis of laryngeal and hypopharyngeal lesions, especially using HDTV NBI.